Interaction of Meloidogyne incognita and Fusarium oxysporum in carnation and physiological changes induced in plants due to the interaction (SAARC Journal of Agriculture, 2016)
Two pot culture experiments were carried out in carnation var. redking in two different seasons to study the interactive effect of Fusarium oxysporum and Meloidogyne incognita on the growth, yield and changes in physiological parameters of the plant. Highest reduction of growth and yield parameters were observed in the plants that received sequential inoculation of the nematode followed by fungus. Significant reduction in the nematode population was observed in the sequential inoculation of the fungus followed by nematodes and combined inoculation of the two pathogens. Reduced chlorophyll content and increased protein and sugar content were observed in the plants due to the interaction of nematode and fungus.SAARC J. Agri., 14(1): 59-69 (2016)